Hubungan Gender dan Usia terhadap Clinical Outcomes pasien COVID-19 di RS HL Manambai Abdulkadir - Hendri Purwadi (Jurnal Kesehatan dan Sains, 2022)
Background: COVID-19 has impact on increasing fatlity and mortality rate worldwide. The mortality rate of COVID-19 in Manambai Abdulkadir was 19% througout 2021. Objective: The aims of this study was to analyze the relationship between gender, age and the clincial outcomes of COVID-19. Method : A quantitative study with retrospective design was applied. A total sampling study has been used to analyse 428 medical records of COVID19 patients in HL Manambai Abdulkadir hospital. A chi-square has been used as a statistical analysis. Result: The reuslt showed that majority of COVID-19 patient was male (52,3%) with the age under 60 years old (73,6%). The number of mortality rate was 19,9%. Gender has no relationship with clinical outcomes (p-value: 0,153), meanwhile age has signficant relationship with clincal outcome (p value: 0,03 , OR: 2,67). Recomandation: Need more strict supervision and observation to the elderly COVID-19 patients in the hospital